2020
DOI: 10.15835/nbha48211862
|View full text |Cite
|
Sign up to set email alerts
|

The influence of meteorological factors on the dynamic of Ambrosia artemisiifolia pollen in an invaded area

Abstract: The aim of the present study was to analyse the effect of weather conditions on Ambrosia artemisiifolia airpollen concentrations in the highly invaded area of western Romania. The investigation of Ambrosia pollen concentrations was carried out from 2000 to 2010 by means of the volumetric method. Ambrosia pollen concentrations had increasing trend over study period. The results of cluster analysis show that two main groups were identified: group A, with lower SPI (2000, 2001, 2002, 2003, 2004, 2007) and group B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Literature data show a significant impact of meteorological factors on the intensity of plant pollen release [24][25][26][27]. The present study demonstrated that not all meteorological factors exerted a significant effect on the pollen seasons of the analyzed plant taxa.…”
Section: Resultsmentioning
confidence: 44%
See 1 more Smart Citation
“…Literature data show a significant impact of meteorological factors on the intensity of plant pollen release [24][25][26][27]. The present study demonstrated that not all meteorological factors exerted a significant effect on the pollen seasons of the analyzed plant taxa.…”
Section: Resultsmentioning
confidence: 44%
“…The study conducted in Kielce in 2021 showed that, although the annual sum and maximum concentrations of hornbeam pollen grains were not high, the pollen season of this plant was substantially longer than in other regions of Poland in previous years [11]. As reported by Ianovici and Bîrsan [25], the concentration of airborne pollen grains may increase with increasing temperature. Hence, the impact of the maximum, minimum, and mean temperature on the oak and hornbeam pollen concentration in the air was analyzed in the present study.…”
Section: Resultsmentioning
confidence: 95%
“…Interesting data referring to the correlation between pollen concentration and meteorological parameters from the Western region of Romania were presented in another recent local study, showing that Ambrosia pollen concentrations was positively associated with high temperature and sunshine hours and inversely associated with relative humidity [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…In turn, the research carried out by Rodinkova et al [59] indicates that an elevated mean daily temperature accelerates the start of the Ambrosia pollen season. Ianovici and Birsan [66] reported a significant negative correlation of Ambrosia pollen concentrations with relative humidity. The results presented by Šaulienė and Veriankaitė [67] indicate that the presence of airborne Ambrosia pollen in Lithuania was accompanied by approximately 70% relative air humidity and the minimum air temperature not less than 12 • C. In turn, it has been found that droughts may also significantly decrease Ambrosia pollen season, as reported from Ukraine by Rodinkova et al [59].…”
Section: Ambrosia Pollen Seasonsmentioning
confidence: 95%